Evaluación de las propiedades físicas y químicas del suelo en acacia (acacia melanoxylon) con la siembra en contorno de cuatro leguminosas, en entisoles de terraza de banco, Campus Salache, 2022. - Chancusig Casa, Diana Gabriela (2022)
The present research was carried out in order to evaluate the behavior of the physical and chemical properties of the forest species Acacia (Acacia melanoxylon) with the contour planting of four leguminous plants such as: Vicia (Vicia sativa), lentil (Lens culinaris), bean (Phaseolus vulgaris) and pea (Pisum sativum), by means of a (DCA), with 5 treatments and 4 replications, ADEVAS and Tukey tests at 5% were performed, in the germination percentage the best was A2 with 94.25%; A3 obtained better results in the variables: diameter (0.65mm), height (94cm), soil weight (65.83kg), number of branches (21), main root length (58.6cm), number of secondary roots (36), forest root weight (15.63), forest root volume (27.1cm³), crown volume (151.83cm³), legume root weight (912, 5kg), legume root volume (227.2 cm³), in the chemical properties, the pH of the initial analysis was 9.34 for A3, while the final analysis was 8.17, in the organic matter the initial analysis was 0.42%, and at the end it rose to 0.6% in the case of A2 and A3; N was 10 ppm in the initial analysis, while in the final analysis it increased to 22ppm in A3, P in the initial analysis was 8.2 ppm, in the final analysis in A3 it increased to 24ppm; K according to the initial analysis was 3.26 meq/100ml, in the final analysis it increased to 3.99 meq/100ml being the A3 with the highest value, in Ca the initial analysis was 22.95 meq/100ml, in the final analysis Ca was maintained being the A3 with the highest value of 25.48 meq/100ml, in the physical properties texture was maintained in loam; for bulk density in the depths of: 10-20-30 cm the highest value is 1.33g/ml; in the real density presents a value of 2.29g/ml; and the porosity of the highest value is a value of 51.3%; the porosity for an adequate development of plants in loam soils is 35%.